Pseudokarst caves of the Outer Western Carpathians, Czechia. Issue 2 (30th November 2017) - Lenart, Jan; Miklín, Jan
ABSTRACT: The paper presents complex results of a dataset related to the pseudokarst caves in the area of the Czech Outer Western Carpathians. We collected the data from all 130 discovered and described caves of different types and dimensions in various geomorphic units and lithologies. We mainly focus on the results of the morphometric parameters of the caves as well as of the areas with their entrances. The final map sheet presents the Main Map with the position of the caves, their size category, type, classification of the position within the slope deformation and natural protection status. Moreover, the final map sheet also contains a supplementary map of the distribution of the caves, diagrams of their morphometric parameters, detailed maps of Mraznica and Cyrilka Caves, a graph of overwintering bat species in Cyrilka Cave and structural measurement diagrams. The map is intended to be used as introductory material into the problems of pseudokarst caves.